2015
DOI: 10.1016/j.ypmed.2014.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Medical school curriculum characteristics associated with intentions and frequency of tobacco dependence treatment among 3rd year U.S. medical students

Abstract: Objective Physicians play a critical role in addressing tobacco dependence, yet report limited training. Tobacco dependence treatment curricula for medical students could improve performance in this area. This study identified student and medical school tobacco treatment curricula characteristics associated with intentions and use of the 5As for tobacco treatment among 3rd year U.S. medical students. Methods Third year medical students (N=1065, 49.3% male) from 10 U.S. medical schools completed a survey in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…This study found that the 5A behaviors of nursing internship students helping smokers quit were associated with tobacco cessation education [18] and the preceptors’ 5A behaviors, as well as tobacco knowledge and 5As self-efficacy. This result is consistent with that of previous studies [33,34,35,36], as well as Behavior Change Theory such as the social cognitive theory and the theory of planned behavior [37,38,39,40,41,42].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study found that the 5A behaviors of nursing internship students helping smokers quit were associated with tobacco cessation education [18] and the preceptors’ 5A behaviors, as well as tobacco knowledge and 5As self-efficacy. This result is consistent with that of previous studies [33,34,35,36], as well as Behavior Change Theory such as the social cognitive theory and the theory of planned behavior [37,38,39,40,41,42].…”
Section: Discussionsupporting
confidence: 93%
“…The questionnaire was revised from the literature [31,32,33] and modified several times after discussions with experts and two preliminary investigations. Eligible questionnaire would be rewarded with „1 attached to the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Multimodal training strategies, including role-playing scenarios as well as seeing preceptors as positive role models, may also help in changing attitudes and teaching appropriate cessation treatments. 26,58 Because physicians continue to be viewed with great respect by the Argentine public, their lack of awareness of this fact may partially explain the high smoking rate in this population, and may project them as negative role models. Medical schools not only need to implement changes in the medical curricula, but also need to develop cessation programs among their students.…”
Section: Discussionmentioning
confidence: 99%
“…25 Smoking prevalence among US students in the health profession is close to 7 %. 26 In Europe, it ranges from 3.8 % in Wales 27 to 22.1 % in Germany 28 ; in Asia, from 2.1 % in Thailand 29 to 66.9 % among Chinese men. 30 Among Latin American countries, it was estimated that 16.9 % of Brazilian Electronic supplementary material The online version of this article (doi:10.1007/s11606-016-3890-0) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…Afterwards, lots of schools launched relative education among students including nursing and medical students [13][14][15] . Then some studies began to explore the effect of characteristics of courses on the conception and knowledge of students in helping smokers to quit [16] .…”
Section: Introductionmentioning
confidence: 99%